Macrozoobenthos Community Structure in Rivers Receiving Tofu Industry Wastewater in Madiun Regency - Nastiti, Diah Ayu Widya; Setyono, Prabang; Budiharjo, Agung (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the macrozoobenthos community structure in two rivers receiving tofu industry wastewater and to examine its relationship with aquatic environmental conditions. Sampling was conducted using purposive sampling at six stations representing upstream, impacted, and recovery zones. Macrozoobenthos community structure was assessed using ecological indices, the Biological Monitoring Working Party–Average Score Per Taxon (BMWP-ASPT), Bray–Curtis similarity analysis with Unweighted Pair Group Method with Arithmetic Mean (UPGMA) clustering, and Canonical Correspondence Analysis (CCA). The results showed that stations receiving direct inputs of tofu industry wastewater exhibited greater biological stress than the upstream and recovery zones. This pattern was characterized by the dominance of the family Thiaridae, a taxonomic group tolerant of organic pollution, and lower BMWP-ASPT scores at stations directly receiving wastewater inputs. BMWP-ASPT values indicated biological conditions ranging from lightly to moderately polluted. Bray–Curtis UPGMA analysis revealed clustering of communities according to similarities in community structure among stations. CCA indicated a tendency toward an association between macrozoobenthos community structure and environmental parameters; however, the overall relationship was not statistically significant (p = 0.139). These findings suggest that macrozoobenthos community structure has potential as a biological indicator for rivers receiving tofu industry wastewater, although its association with the measured environmental parameters was not statistically significant.